«Je est un autre». Autobiography and self-commentary by proxy (2001) followed by Interpo-sitions (2024) (inOpera Esercizi di lettura su testi contemporanei, 2024)
Between 1997 and 2000, the publication of "Meridiani" of poets born in the 1910s and 1920s (Attilio Bertolucci, Mario Luzi, Andrea Zanzotto and Giovanni Giudici), published with the authors still alive and working, led to the redefinition of the commentary on the texts,  to which the authors contributed. The article dedicated in 2001 to this phenomenon is reread by retracing the episodes in which poets of subsequent generations (analyzed are the cases of Milo De Angelis, Claudio Damiani, Fabio Pusterla, Valerio Magrelli, Marcello Frixione and Lello Voce) have bent to their poetic needs spaces previously the prerogative of second and third figures.
Keywords: Poetry publishing; Self-commentary; Poetics